Novel Bioengineered Cassava Expressing an Archaeal Starch Degradation System and a Bacterial ADP-Glucose Pyrophosphorylase for Starch Self-Digestibility and Yield Increase - Ligaba-Osena, Ayalew; Jones, Jenna; Donkor, Emmanuel; Chandrayan, Sanjeev; Pole, Farris; Wu, Chang-Hao; Vieille, Claire; Adams, Michael W. W.; Hankoua, Bertrand B. (Frontiers in Plant Science, 2018)
To address national and global low-carbon fuel targets, there is great interest in alternative plant species such as cassava (Manihot esculenta), which are high-yielding, resilient, and are easily converted to fuels using the existing technology. In this study the genes encoding hyperthermophilic archaeal starch-hydrolyzing enzymes, -amylase and amylopullulanase from Pyrococcus furiosus and glucoamylase from Sulfolobus solfataricus, together with the gene encoding a modified ADP-glucose pyrophosphorylase (glgC) from Escherichia coli, were simultaneously expressed in cassava roots to enhance starch accumulation and its subsequent hydrolysis to sugar. A total of 13 multigene expressing transgenic lines were generated and characterized phenotypically and genotypically. Gene expression analysis using quantitative RT-PCR showed that the microbial genes are expressed in the transgenic roots. Multigene-expressing transgenic lines produced up to 60% more storage root yield than the non-transgenic control, likely due to glgC expression. Total protein extracted from the transgenic roots showed up to 10-fold higher starch-degrading activity in vitro than the protein extracted from the non-transgenic control. Interestingly, transgenic tubers released three-fold more glucose than the non-transgenic control when incubated at 85oC for 21-h without exogenous application of thermostable enzymes, suggesting that the archaeal enzymes produced in planta maintain their activity and thermostability.